2020
DOI: 10.1080/19491247.2020.1805147
|View full text |Cite
|
Sign up to set email alerts
|

Is ‘informal’ housing an affordability solution for expensive cities? Evidence from Sydney, Australia

Abstract: Does 'informal' housing offer more affordable choices for low-income renters in expensive cities? This paper investigates this question with reference to Sydney, Australia, where planning reforms have sought to deregulate housing development including 'informal' and low cost market accommodation, in response to chronic housing affordability pressures. Examining rental advertisements, housing supply and affordability data, and through interviews with local government personnel, we find that informal secondary u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Synthesising the regulatory aims and practical understanding, the magnitude of monetary sanction is central in deterring violations against building regulations (including the production of substandard housing). In the same vein, several studies on housing regulation in Australia [12,13], Czechia [75,76] and the United Kingdom [77] suggest that illegal housing production results when the risks of penalty are outweighed by the expected profitability. Considering the failure of building control, we particularly draw on Vols and Belloir's [56] qualitative findings in investigating the rogue landlords who frequently infringe on building control regulations in the Netherlands.…”
Section: Applicability Of the Game-theoretical Models On Explaining T...mentioning
confidence: 99%
See 3 more Smart Citations
“…Synthesising the regulatory aims and practical understanding, the magnitude of monetary sanction is central in deterring violations against building regulations (including the production of substandard housing). In the same vein, several studies on housing regulation in Australia [12,13], Czechia [75,76] and the United Kingdom [77] suggest that illegal housing production results when the risks of penalty are outweighed by the expected profitability. Considering the failure of building control, we particularly draw on Vols and Belloir's [56] qualitative findings in investigating the rogue landlords who frequently infringe on building control regulations in the Netherlands.…”
Section: Applicability Of the Game-theoretical Models On Explaining T...mentioning
confidence: 99%
“…This view challenges the usefulness of social-cultural deterrent theories that are built upon morality and ethics. Numerous grounded studies have suggested that the growth of informal and illegal dwellings is attributed to profitability and speculation [13,64,75,76]. Conceivably, classic criminologi-cal theories based on the rational choice model seem to offer a better explanation of the game between enforcers and property owners who produce ISUs.…”
Section: Deterrent Effects Of Building Enforcement: Certainty Severit...mentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, in Sydney, Gurran et al (2020) found that short term rental (STR) platforms such as Airbnb typically rented to the more affluent sector of the rental market and provided limited affordable alternatives to formal rental stock. Hence, there is increasingly criticism over the ramifications of Airbnb's presence in the housing market, given housing affordability is already a critical concern in many urban areas where tourism thrives (Lee, 2016).…”
Section: Introductionmentioning
confidence: 99%